Reduksi Pernikahan Dini melalui Pendidikan Islam di Desa Sukorejo Ponorogo - Kurnia Rahmadani, Muhamad Indi; Ayu, Diyan Putri; Kadenun, Kadenun (Institut Agama Islam Sunan Giri Ponorogo, 2024)
The Early marriage in Sukorejo Village, triggered by tradition, social pressure, and economic conditions, has an impact on children's education. This study aims to determine the effect of early marriage on children's education in the village, with a focus on aspects of formal education, access to further education, awareness of the importance of education, and psychological and emotional impacts. Qualitative research methods with a phenomenological approach were used to explore community views and the effects of early marriage. Data were collected through interviews, participant observation, and documentation. The results of the study showed that early marriage resulted in the termination of formal education, loss of access to further education, and decreased motivation to learn. The psychological and emotional pressures experienced by children who marry early also affect the effectiveness of their education. In addition, lack of education worsens employment opportunities and increases the risk of poverty. This study is expected to raise public awareness of the importance of education and readiness for marriage, as well as support to reduce the number of early marriages in order to improve the future of the younger.